(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aimed to evaluate the influence of Advertising Services (ADS) and Celebrity Endorsement (CE) on Purchase Interest (PI) among students as active users of online shopping platforms. A quantitative research design was employed, utilizing a survey method distributed to the student population. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to assess both the measurement and structural models. The results revealed that Advertising Services had a statistically insignificant effect on purchase interest. In contrast, Celebrity Endorsement had a significant positive impact and was identified as the dominant driver of consumer interest in this study. The structural model demonstrated satisfactory explanatory power and established predictive relevance for the variables involved. These findings suggest that for the student segment, the presence of a credible public figure is more effective in stimulating purchase interest than traditional advertising services. Consequently, online shop operators should prioritize selecting highly credible endorsers who resonate with the target audience to optimize promotional effectiveness.